Effect of cloprostenol injections on oestrus behaviour of Kedah-Kelantan cattle - Dahlan, I.; Mohamad, N.; Tan, H. S. (Institut Penyelidikan dan Kemajuan Pertanian Malaysia, 1985)
This study was conducted to investigate the oestrus behaviour of Kcdah-Kclantan (KK) cattle following oestrus synchronization using the prostaglandin analogue. cloprostcnol (Estrumate. ICI). A total of 136 KK females received two intra-muscular injections of c1oprostenol. II days apart. with a dose of 0.5 mg per injection. The animals were allotted randomly into one of three observational groups as follows: Group I - (n = 75) was visually observed for five hours once daily from 0730 to 1230 hours; Group II - (n = 32) was observed for oestrus twice daily from 0730 to 0930 hours and 1730 to 193O hours; Group III - (n = 29) was detected for behavioural oestrus continuously for six days following the second prostaglandin injection. Twice daily oestrus detection was more effective in observing standing oestrus than once daily detection. Continuous observation detected 97% standing oestrus in the group. Percentages of females in oestrus following the first and second prostaglandin injections were 72.8% and 75.0% respectively. Only about 29% of animals that stood to be mounted showed a clear vaginal mucus discharge. The mean on set of oestrus following the second prostaglandin injection for KK heifers and cows were 54.2 ± 16.5 hours and 53.7 ± 17.7 hours respectively. The duration of oestrus of KK females was about 22 hours. Heifers showed less intense behavioural oestrus than cows. The oestrus activity of KK female was not significantly affected by ambient temperature (r = -O.28) out positively related to relative humidity (r = 0.41). Mean serum progesterone concentration dropped from 2.1 ± O.94ng/ml to 0.04 ± 0.03 ng/ml within 24 hours following the prostaglandin injection and remained at basal levels throughout the sampling period. Two females (one cow and one heifer) failed to respond to the second prostaglandin injection due to the absence of functional luteal tissue.